Overview of Academic Stress of FPIP Psychology Study Program Students Programming Thesis Courses in 2017/2018: Gambaran Stres Akademik Mahasiswa Prodi Psikologi FPIP Yang Memprogram Mata Kuliah Skripsi Tahun 2017/2018 - M. Iqbal Hakiki; Lely Ika Mariyati (Universitas Muhammadiyah Sidoarjo, 2020)
The aim of this research is to find out the academic stresses of psychology study program students who are programming thesis courses, faculty of psychology and education at Muhammadiyah University of Sidoarjo. The method in this study uses a descriptive quantitative approach which aims to determine the intensity of academic stress on psychology students who are programming thesis courses. The research subjects were 123 out of 200 students who processed thesis courses in 2017-2018. The sample was taken using simple random sampling. The data were collected using the academic stress scale compiled by the researcher. The results of this study illustrate that the results of the intensity of student academic stress are dominated in the moderate to quite high category, namely 67%. The results of this study also illustrate that the aspects of academic stress in psychology study program students are more dominant in the physical and emotional aspects. On the physical aspect, you get 34%, on the emotional aspect you get 29% on the intellectual aspect you get 21% and on the intrapersonal aspect you get 16%.